A novel method for evaluating the effect of pollution on the human skin under controlled conditions - Curpen, Seerooven; Francois‐Newton, Veronique; Moga, Alain; Hosenally, Muzzammil; Petkar, Gitanjali; Soobramaney, Vitisha; Ruchaia, Bryna; Lutchmanen Kolanthan, Vimi; Roheemun, Naailah; Sokeechand, Bibi N.; Aumeeruddy, Zaahira; Ramracheya, Reshma D. (Skin research and technology, 2020)
Background Generally considered as a major risk factor for various respiratory diseases, air pollution can also have a significant impact on the skin. To date, there is a plethora of cosmetics products with “anti‐pollution” claims. However, these claims have not been fully substantiated with robust scientific evidence and currently there is no standardized method in place for validating the anti‐pollution efficacy of cosmetics products. Materials and Methods This article discusses an innovative Controlled Pollution Exposure System (CPES) which allows quantified administration of pollutants on the skin and analysis of their direct impact. Using CPES, human subjects were exposed to ambient dust and ozone and sebum were sampled and analyzed for biomarkers. Results Following exposure of human subjects’ skin to either ambient dust(100‐450 μg/cm3) or ozone(100‐1000 ppb), analysis of sebum revealed a significant decrease in squalene concentration, and significant increases in squalene monohydroperoxide and malondialdehyde concentration. Conclusion The findings demonstrate cutaneous oxidative stress induced by ambient dust and ozone. The findings also demonstrate the efficacy of CPES to accurately measure the direct effect of controlled gaseous and particulate pollutants on human skin and indicate that squalene, squalene monohydroperoxide and malondialdehyde may serve as potent biomarkers for evaluating potential anti‐pollution claims of cosmetics products.